2018
DOI: 10.2147/jmdh.s155352
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based child protection teams that care for parents who abuse or neglect their children recognize the need for multidisciplinary collaborative practice involving perinatal care and mental health professionals: a questionnaire survey conducted in Japan

Abstract: BackgroundChild abuse and/or neglect is a serious issue, and in many cases, parents are the perpetrators. Hospital-based child protection teams (CPTs) play pivotal roles in the management of not only abused and/or neglected children but also of their parents; this is generally conducted through multidisciplinary practice. The aim of this study is to survey hospital-based CPT members to determine the professions they perceive to be most applicable to participation in CPTs.Participants and methodsThe participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Some teams initiated voluntary referrals to health care and support services, for example, in Israel (Benbenishty et al, 2014) and the United States (Kistin et al, 2011). Teams in the Netherlands (Teeuw et al, 2017), Japan (Okato et al, 2018), and Hong Kong (Lo et al, 2017) had a leading role in deciding on welfare and support plans for children and their families. Thus, while for some teams’ recognition of possible SCAN was the end of the process, for others it was only the beginning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some teams initiated voluntary referrals to health care and support services, for example, in Israel (Benbenishty et al, 2014) and the United States (Kistin et al, 2011). Teams in the Netherlands (Teeuw et al, 2017), Japan (Okato et al, 2018), and Hong Kong (Lo et al, 2017) had a leading role in deciding on welfare and support plans for children and their families. Thus, while for some teams’ recognition of possible SCAN was the end of the process, for others it was only the beginning.…”
Section: Resultsmentioning
confidence: 99%
“…However, only about a quarter ( n = 6 studies) of the studies in this review actually approached professionals and collected information directly from them. The methodologies used in these studies explored professionals’ working-together experience, including data gathering using a questionnaire, Delphi approach, a task-tracing instrument, and rapid improvement events (Balsley et al, 2019; Kistin et al, 2010; Okato et al, 2018; Ross et al, 2019) as well as two studies that used semistructured interviews (Itzaky & Zanbar, 2014; Svärd, 2014). These studies emphasized the importance of professionals’ feedback on their everyday practice and its crucial contribution to meeting key goals such as: identifying weak links in the workflow: For example, indicate on communication gaps in the habitual way the work is carried out (Balsley et al, 2019); uncovering insufficient expertise: -For example, competence and skills around particular patient populations, such as pregnant women (Okato et al, 2018) or patients with reported sexual abuse (Hoehn et al, 2018); direct improvement efforts to meet workforce needs: For example, when professionals voiced the importance of encouraging active interprofessional collaboration and team collegiality, as well as investment of hospital’s resource (Kistin et al, 2010); and detecting unexpected and unwanted outcomes of reforms: -Such as limited investment of time by in-hospital social workers in CPTs CM activities (Ross et al, 2019) following the introduction of a care coordination strategy leading, escalation in power struggles and friction between social workers and physicians following an increase in physicians’ confidence dealing with SCAN following training (Itzaky & Zanbar, 2014), and the impact of institutionalized norms of action (e.g., juridical, therapeutic, or medical) on the role or position (i.e., active, passive, or reflective) social workers took in CPTs (Svärd, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a retrospective cohort study based on the medical records of all consecutive pregnant women with psychosocial problems that met the following inclusion criteria: 1) continuously visited and gave birth at the department of maternal-fetal medicine, at the Chiba University Hospital between February 2018 to March 2019; and 2) received an intervention from the hospital-based child protection team (CPT), which plays a crucial role in the management of abused or neglected children and their abusive or negligent families 19. Hospital-based CPTs were not only proactively involved in cases of child maltreatment but also during the prenatal period for pregnant women with psychosocial problems, who are, along with their partners and families, at risk of engaging in child maltreatment 19. At Chiba University Hospital, midwives and obstetricians screen all pregnant women during their first visit to determine the presence of any psychosocial problems using clinical interviews and a questionnaire sheet regarding their medical and sociodemographic information as a part of the study recruitment.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…A multidisciplinary approach from multi-agency partnerships is a standard in the prevention of child maltreatment [6,7]. Given that early interventions, such as those conducted by nurses visiting new parents and pregnant women at risk of child maltreatment, are effective methods for preventing child maltreatment [8], it is important that multidisciplinary workers who belong to the agencies involved with families and pregnant women at risk of child maltreatment are aware of the early signs of child maltreatment [5,9].…”
Section: Introductionmentioning
confidence: 99%